Desain dan Implementasi Alat Praktikum Kalorimeter Berbasis IOT (Internet of Things) Modul Esp8266 dengan Menggunakan Aplikasi Blynk - Hafiz, Kemas Muhammad; Sundari, Ella; Annas, Adian Aristia (Innovative: Journal Of Social Science Research, 2025)
This research develops an IoT-based calorimeter practical tool using the ESP8266 module and the Blynk application to increase the accuracy and efficiency of heat transfer measurements. This tool utilizes the DS18B20 and DHT11 sensors to measure temperature and humidity in real-time, with data sent via the Blynk application. Test results show that this tool has high accuracy and is superior to conventional calorimeters in terms of efficiency and ease of use. ANOVA analysis indicated that the temperature of the liquid had a significant influence on the measurement results, while the type of solid did not show a significant influence. This tool is expected to improve the quality of learning and research in the field of physics